Impact of esophagectomy for cancer on patients' occupational status. Issue 1 (January 2016) - Pinto, E.; Cavallin, F.; Alfieri, R.; Saadeh, L.M.; Mantoan, S.; Cagol, M.; Castoro, C.; Scarpa, M.
Abstract: Background: The aim of our study was to investigate the impact of esophagectomy for cancer on patients' occupational status. Methods: All 109 consecutive patients presenting with esophageal cancer to the Surgical Oncology Unit of the Veneto Institute of Oncology Padua (Italy) between November 1, 2009 and March 15, 2012, were included in the study. Information on occupational status at diagnosis and at 1 year after esophagectomy was retrieved. Health-related quality of life was evaluated at discharge after surgery using selected aspects of the EORTC QLQ-C30 questionnaire. Non parametric statistics were used. Results: Sixty-one patients (49.6%) were active workers at diagnosis and 50 of them (82.0%) underwent esophagectomy. Eighteen active workers (18/50, 36.0%) quit their job within one year from esophagectomy. They received jejunostomy more often than patients still working after surgery (50.0% vs. 18.8%, respectively; p = 0.03) and reported lower social functioning at discharge (mean ± SD 63.6 ± 16.4 vs. 80.2 ± 25.6 in others, p = 0.02). Multivariable analysis identified jejunostomy as independent predictor of job-quitting at 1 year after esophagectomy (p = 0.03; OR 4.75, 95% C.I. 1.11–20.39) but not social functioning at discharge (p = 0.21). Conclusions: Patients should be informed that they may experience social and work disability due to cancer treatment and adequate interventions of return-to-work support should be provided. Adequate welfare strategy should be implemented for esophageal cancer survivors, enhancing their role competences and contributing to precision care medicine.